PENGARUH KEBERSIHAN TERHADAP KENYAMANAN BERIBADAH DI MASJID ATTAQWA 2 KADIPIRO SURAKARTA - Bertha Ayu Kencana; Adnan Rio Rizqullah; Calvin Maurhent Fernando Bangun; Laraswati (LPPM Universitas Nias Raya, 2025)
This study aims to examine the influence of the cleanliness of the environment at Masjid Attaqwa 2 Kadipiro Surakarta on the comfort of worshippers during religious practices. Cleanliness is one of the essential factors that can affect focus and comfort in performing worship. The method used in this study is a quantitative approach, with data collected through direct observation. The results show that the level of mosque cleanliness significantly affects worship comfort. A clean mosque environment including the prayer area, ablution space, and other facilities has a positive effect on the worshippers' perception of comfort. Worshippers who feel that the mosque environment is clean tend to experience greater tranquility, comfort, and satisfaction during worship. Conversely, a dirty or poorly maintained environment can disturb comfort, thereby lowering the quality of the worship experience. These findings emphasize the importance of regular mosque cleanliness management and community involvement as part of the effort to enhance the quality of worship for the congregation.